Numerical Simulations of a Polydisperse Sedimentation Model by Using Spectral WENO Method with Adaptive Multiresolution (2016)
In this work, we apply adaptive multiresolution (Harten's approach) characteristic-wise fifth-order Weighted Essentially Non-Oscillatory (WENO) for computing the numerical solution of a polydisperse sedimentation model, namely, the Höfler and Schwarzer model. In comparison to other related works, time discretization is carried out with the ten-stage fourth-order strong stability preserving Runge-Kutta method which is more efficient than the widely used optimal third-order TVD Runge-Kutta method. Numerical results with errors, convergence rates and CPU times are included for four and 11 species. © 2016 World Scientific Publishing Company.